Integrated Safety Management for Mass Arts and Entertainment Events Based on an Outdoor Concert in Poland: A Case Study - Sułek, Katarzyna (Journal of Public Governance, 2023)
Objective: This article aims to conduct a detailed analysis of the activities carried out within the framework of integrated safety management of a specific arts and entertainment event. Moreover, it seeks to verify the hypothesis that the security sequence applied during the individual phases of the event, based on changes in the number of security and information services, ensures an appropriate level of safety for the participants.Research Design & Methods: The study utilised a case study methodology in conjunction with in-depth interviews and document analysis techniques for data collection and analysis. The utilisation of this diverse array of research methods facilitated the acquisition of a holistic understanding of the processes that support the maintenance of public order during the event. Additionally, it enabled the evaluation of the practical effectiveness of integrated security management.Implications/Recommendations: The implications of this study extend to the realm of public governance. It highlights the need for robust regulatory frameworks to effectively manage mass events. The law plays a crucial role in establishing guidelines and standards for ensuring participant safety and public order. Moreover, effective coordination between different stakeholders, including event organisers, security services, and information providers, is essential to achieve an appropriate level of safety.Contribution/Value Added: This article contributes to the understanding the importance of integrated safety management in mass events and its implications for entities organising mass events. It provides valuable insights into the processes and measures necessary to maintain public order and ensure participant safety. By addressing the gaps in knowledge regarding safety management systems for mass events, it offers recommendations for policymakers, event organisers, and other stakeholders involved in public governance.